Differential investigations from plasma‐derived and recombinant Factor IX revealed major differences in post‐translational modifications of activation peptides. Issue 2 (10th September 2012) - Chevreux, G.; Faid, V.; Andre, M.‐H.; Tellier, Z.; Bihoreau, N.
<x xml:space="preserve">Abstract</x> Post‐translational modifications (PTMs) located on the activation peptide (AP) of recombinant FIX (rFIX, BeneFIX®) and plasma‐derived FIX (pdFIX, Betafact®) have been investigated by mass spectrometry to review the structural differences between these two products. Three major structural differences were pointed out. rFIX contains a low amount of phosphorylated and sulphated AP (4% for rFIX vs. 70% for pdFIX); rFIX N‐glycans are only sialylated in the α2‐3 linkage, whereas pdFIX N‐glycans contain both type of α2‐3 and α2‐6 linkages, and rFIX does not contain any sialyl LewisX glycoantigens contrary to pdFIX. These variations might participate in the in vivo potential different behaviours of the two molecules.